Sacred Symbols in Dimitrie Gavrilean’s Paintings - Emilian Adrian Gavrilean (Anastasis: Research in Medieval Culture and Art, 2016)
This year, on the 12th of July, there are four years since the passing away of the painter Dimitrie Gavrilean who, ,”through the unique impresion of his originality, early became an emblem of the school of painting of Iasi.” Born in Voroneţ, in 1942, Dimitrie Gavrilean attended ”Nicolae Grigorescu” Academy of Arts of Bucharest, being an eminent disciple of the master Corneliu Baba. The work in the creation workshop was combined with the vocation of teacher at the Faculty of Visual Arts and Design within ”G. Enescu” University of Arts of Iaşi, being a rector of this institution in the period 2000-2004. In the contemporary plastic landscape, the artistic work of the painter Dimitrie Gavrilean (1942-2012) from Iaşi occupies a special place. It mirrors the utmost of the autochthonous rural imaginary, the Romanian fundamental myths, the ancestral myths as well as the recently Christianized ones. His vision is specific to the Romanian Christianity and the Byzantine iconography. The language of Gavrilean’s paintings is one of symbols, by excellence. As Emil Staco rightfully observed, the entire work of art of master Gavrilean is ”a work of art of the symbols, of the metaphors rooted in the spirituality of the Romanian village of Bukovina, in the frescoes of Voroneţ and Humor Monasteries.” On the one hand, the painter did not content himself with illustrating only the ancestral mythical world by means of symbols with universal valences, but he got actively involved in the Christian valorization of mythical symbols. On the other hand, by integrating sacred symbols (the dove, the cock, winged characters, the wise old man, the architecture-church, the sun, Voroneţ blue) of the Christian iconography of Byzantine tradition in paintings not necessarily religious, Dimitrie Gavrilean pushed his work of art to the border between sacred and profane, proving an extraordinary capacity of spiritualizing matter as well as of materializing the spirit through art.